Analisis Common Size dan Rasio Keuangan Perusahaan Sektor Industri Barang Konsumsi di BEI - Trisa Inna Fitriyani; Zulkarnain Zulkarnain (UNHI Press, 2020)
This analysis is carried out aiming to see the performance of the consumer goods industry/ CGI sector listed on the Indonesia Stock Exchange (IDX) using common size analysis and financial ratio analysis. The research method used in this research is descriptive research method. The data used is secondary data, in the form of CGI sector financial statements for the period 2017-2018, which are published on the IDX website. The data used is the financial statements of 53 companies. The source of the theory is obtained through library research and similar research obtained from research journals. Financial ratio analysis used is the current ratio, quick ratio, debt to assets, debt to equity, total asset turnover, fixed asset ratio, gross profit margin, return on assets, and return on equity. The analysis shows an increase and a decrease, and a stable number for the results.